Observation of the decay B0s→[phi]π+π− and evidence for B0→[phi]π+π− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physical review, 2017)
The first observation of the rare decay B0s→ϕπ+π− and evidence for B0→ϕπ+π− are reported, using pp collision data recorded by the LHCb detector at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. The branching fractions in the π+π− invariant mass range 400<m(π+π−)<1600 MeV/c2 are [3.48±0.23±0.17±0.35]×10−6 and [1.82±0.25±0.41±0.14]×10−7 for B0s→ϕπ+π− and B0→ϕπ+π− respectively, where the uncertainties are statistical, systematic and from the normalization mode B0s→ϕϕ. A combined analysis of the π+π− mass spectrum and the decay angles of the final-state particles identifies the exclusive decays B0s→ϕf0(980), B0s→ϕf2(1270), and B0s→ϕρ0 with branching fractions of [1.12±0.16+0.09−0.08±0.11]×10−6, [0.61±0.13+0.12−0.05±0.06]×10−6 and [2.7±0.7±0.2±0.2]×10−7, respectively.